2021
DOI: 10.4149/neo_2021_201204n1304
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog is a novel prognostic biomarker in patients with oral squamous cell carcinoma

Abstract: Recent studies revealed that Sonic Hedgehog (SHH) signaling pathway plays an important role in initiation and tumor progression in various malignancies, however, its role in oral squamous cell carcinoma (OSCC) remains unclear. The objective of this study was to investigate the prognostic significance of SHH expression in patients with OSCC in relation to p53 protein expression and HPV (Human Papilloma Virus) presence. SHH, p53, HPV expression was analyzed in surgical specimens from 70 patients with primary OSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Several studies have demonstrated that the HH pathway plays a crucial role in tumor growth and invasion in HNSCC. Therefore, increased expression of SHH, PTCH1, SMO, GLI1, GLI2, and GLI3 was detected significantly more frequently in advanced HNSCC tumors [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In most cases, progressing HNSCC invades the mandible or maxilla, what leads to bone destruction.…”
Section: Aberration Of Hh Signaling Pathway In Hnsccmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated that the HH pathway plays a crucial role in tumor growth and invasion in HNSCC. Therefore, increased expression of SHH, PTCH1, SMO, GLI1, GLI2, and GLI3 was detected significantly more frequently in advanced HNSCC tumors [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In most cases, progressing HNSCC invades the mandible or maxilla, what leads to bone destruction.…”
Section: Aberration Of Hh Signaling Pathway In Hnsccmentioning
confidence: 99%
“…The correlation between the expression of HH proteins and prognosis in patients with HNSCC is still not well established. Most studies revealed that increased SHH, PTCH1, SMO, and GLI1 expression are significantly correlated with worse OS [ 50 , 57 , 59 , 60 , 67 , 68 ]. Contrary to these results, Enzenhofer et al observed better OS in HPV-negative HNSCC patients with GLI1 and GLI2 overexpression [ 69 ].…”
Section: Aberration Of Hh Signaling Pathway In Hnsccmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, the main treatment methods for OSCC are mainly surgery, chemotherapy, and radiotherapy. The major causes of high mortality are high tumor invasion, lymph node involvement, poor response to therapy, and early local recurrence ( Cierpikowski et al, 2021 ). To be able to effectively improve the survival rate and improve prognosis in patients with OSCC, there is an urgent need to look for a potential biomarker.…”
Section: Introductionmentioning
confidence: 99%